“I feel good in this creative world”: a multi-methods study exploring older artisans’ attributions of mental health, quality of life, and well-being to their work in a UNESCO Creative City of crafts and folk art - Igreja, Sandra; Paúl, Constança; Teles, Soraia (Frontiers in Public Health, 2025)
In the face of global demographic shifts, it is crucial to adopt sustainable solutions that support active and healthy aging. Engagement in creative activities, such as crafts, may positively affect the social determinants of health by promoting mental, physical, and social well-being. While the use of crafts as therapeutic interventions is well documented, research on crafts as a professional activity remains limited, especially among older adults and across different sectors. This multi-methods study combined quantitative data analysis with qualitative exploration of individual narratives to examine how older professional artisans in a UNESCO Creative City of Crafts and Folk Art in Portugal perceive the impact of craftwork on their health and well-being. Fifty-five artisans aged 55 and older took part in walking interviews in their ateliers and completed health and quality of life (QoL) scales (PHQ-8 and WHOQOL-BREF). Thematic content analysis was performed by two independent coders. Participants were 60% men (n = 33) and had a mean age of 67.5 years (SD = 8.02). Each participant was active in one of eight craft sectors represented in the study. The artisans had overall good QoL scores, with the psychological domain showing the highest average (WHOQOL-BREF M = 84.92, SD = 10.98). All but one participant (98.1%) scored below 10 on the PHQ-8, indicating the absence of depressive symptoms. Thematic analysis revealed artisans’ perceptions of both positive and negative impacts of craftwork on their well-being, with 17 areas of impact emerging from their discourses. Positive attributions predominated, with craftwork being associated with psychological well-being, personal and professional fulfilment, creative identity expression and a sense of generativity. In contrast, financial instability and labor precarity emerged as the main strains of craftwork. The study suggests that older artisans understand their professional involvement in crafts and folk art as contributing to their well-being, even in the face of economic challenges associated with this work. These results support policy recommendations, aimed at improving the economic and working conditions of artisans, as well as knowledge transmission programs as strategies to promote active and healthy aging, foster intergenerational learning, and preserve intangible cultural heritage.